Rosmarinic acid as a potential anti-hyperlipidemic agent - Oussama Bekkouch; Ayoub Amssayef; Hamza Elbouny; Mohamed Eddouks; Chakib Alem; Souliman Amrani (Plant Science Today, 2023)
Rosmarinic acid (RA) is a natural phytochemical that occurs in numerous plants, including Rosmarinus officinalis. This bioactive compound is widely reported to exert various pharmacological effects, including anti-hyperlipidemic activity. In this study, we reviewed the literature data on RA and hyperlipidemia research. In silico, in vitro, and in vivo studies were retrieved from Scholar, PubMed, ScienceDirect, Web of Science, and Scopus. The In silico studies revealed that RA possesses squalene synthase and 3-hydroxy-3-methylglutaryl–coenzyme A reductase enzymes inhibiting effect. Additionally, in vitro reports revealed that RA exerts remarkable lipid-lowering effects and also exhibits anti-adipogenic and anti-atherosclerotic activities. The lipid-lowering action was modulated by numerous mechanisms including the regulation of anti-inflammatory and antioxidant signaling pathways. Moreover, in vivo studies revealed that RA alleviates hyperlipidemia in animal models by modulating the expression of genes involved in hyperlipidemia as well as the regulation of gut microbiota and anti-inflammatory pathways. We conclude that RA is a multi-target anti-hyperlipidemic agent. Moreover, we suggest that the use of this bioactive compound as an anti-hyperlipidemic drug would be an effective pharmacological strategy that could provide promising options for the treatment and prevention of hyperlipidemia and its related disorders including atherosclerosis.